Free-weight versus weight machine resistance exercise on pulse wave reflection and aortic stiffness in resistance-trained individuals - Parks, J. C.; Marshall, E. M.; Tai, Y. L.; Kingsley, J. D. (European Journal of Sport Science, 2020)
The purpose of this study was to compare the vascular responses to acute free-weight (FW) resistance exercise (RE) versus weight machines (WM). Thirty-two resistance-trained individuals participated in this study. Both modalities involved performing acute RE and a control. Blood pressure and measures of pulse wave reflection were assessed using pulse wave analysis. Aortic stiffness was assessed using carotid-femoral pulse wave velocity (cf-PWV). A repeated measures analysis of variance was used to determine the effects of modality (FW and WM) and condition (acute RE and control) across time (rest and 10-20 min after exercise) on measures of pulse wave reflection and aortic stiffness. Significance was set a priori at p = 0.05. There were no modality by condition by time interactions for any variable, such that the FW and WM modalities responded similarly across time after acute RE (p > 0.05). There were significant (p = 0.05) increases in heart rate, aortic systolic blood pressure, aortic pulse pressure, augmentation index normalized at 75bpm, and decreases in subendocardial viability ratio (SEVR) after acute RE, compared to rest. There was also a significant (p = 0.05) increase in cf-PWV after acute RE, compared to rest. In conclusion, this study demonstrates that acute free-weight and weight-machine RE are associated with transient increases in measures of pulse wave reflection and aortic stiffness, with reductions in myocardial perfusion. These data demonstrate that both modalities result in significant stress on the myocardium during recovery, while simultaneously increasing pressure on the aorta for at least 10-20 min.